Advanced blood flow assessment in Zebrafish via experimental digital particle image velocimetry and computational fluid dynamics modeling. (March 2020) - Salman, Huseyin Enes; Yalcin, Huseyin Cagatay
Highlights: Zebrafish is an emerging vertebrate model for cardiovascular research. Easy genetic manipulation and embryonic transparency are among its advantages. DPIV enables in vivo imaging of blood flow in Zebrafish embryos. CFD modeling provides detailed analysis of mechanobiological forces. In this review paper, the methods are explained and latest findings are summarized Abstract: Over the past few decades, Zebrafish has become a widely used vertebrate model for cardiovascular research. Easy genetic manipulation, low cost, high fecundity, embryonic transparency, and ability to survive in the early stages of development without active circulation are among the advantages of Zebrafish. Cardiac malformations can be induced through genetic manipulations for elucidating the influence of mechanobiological stimuli on the development and progress of the cardiovascular diseases. For this purpose, a reliable in vivo assessment of cardiac function and disturbed hemodynamics is required. Therefore, it is necessary to accurately determine the complex blood flow patterns and associated hemodynamic shear stresses within the developing heart and cardiovascular system. In the traditional approach, brightfield microscopy is used to track the motion of cells in two-dimensions (2D). However, with the development of advanced modalities such as light-sheet fluorescent microscopy, it is now possible to perform 4D (three-dimensional space + time) imaging of Zebrafish embryo and larvae. The integration of digital particle image velocimetry (DPIV) and computational fluid dynamics (CFD) provide an opportunity for detailed investigations using in vivo images. In this review, DPIV and CFD methods are explained for blood flow assessment, and recent relevant research findings from Zebrafish studies are summarized.